2010
DOI: 10.1149/1.3483787
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Density-of-State on the Temperature and Gate Bias-Induced Instability of InGaZnO Thin Film Transistors

Abstract: The impact of a gate insulator ͑GI͒ material on the device instability of InGaZnO ͑IGZO͒ thin film transistors ͑TFTs͒ was investigated. The IGZO TFTs with SiO 2 GI showed consistently better stability against the applied temperature stress and positive/negative gate bias stress than their counterparts with SiN x GI. This superior stability of the SiO 2-gated device was attributed to the reduced total density of states ͑DOS͒ including the interfacial and semiconductor bulk trap densities. Based on the Meyer-Nel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…In particular, the NBS is much better than those of other reported solution-processed oxide TFTs, including IZO and ZTO:F TFTs81115. Also, ΔV th for PBS is comparable to previously-reported values of the oxide TFTs591028. The negative and positive gate bias temperature stress (NBTS and PBTS) were also measured at an additional thermal stress of 60°C, as shown in Fig.…”
Section: Resultssupporting
confidence: 69%
“…In particular, the NBS is much better than those of other reported solution-processed oxide TFTs, including IZO and ZTO:F TFTs81115. Also, ΔV th for PBS is comparable to previously-reported values of the oxide TFTs591028. The negative and positive gate bias temperature stress (NBTS and PBTS) were also measured at an additional thermal stress of 60°C, as shown in Fig.…”
Section: Resultssupporting
confidence: 69%
“…42 The N it (8.9 Â 10 11 /cm 2 ) of the SiN x -gate device was approximately 3 times higher than that (3.0 Â 10 11 /cm 2 ) of SiO 2 -gated device, which was approximated from the subthreshold gate swing values from both devices. 43 The inferior stability of the nitride device was manifested more clearly under NBIS conditions. Although the V th value for SiN x -gated device was shifted significantly in the negative direction (by 11.6 V), the SiO 2 -gated device exhibited V th movement of only À0.78 V. The consistent inferior stability of the IGZO TFTs with the SiN x gate dielectric is believed to originate from its high N it value, which concurs with the trapping mechanism of the photoinduced hole carriers.…”
Section: Carrier Trapping or Injection Modelmentioning
confidence: 99%
“…Upon decreasing the deposition pressure from 5 to 1 mTorr, the calculated V FB and A values were varied from −2.0 V and 30.8 eV −1 to −1.1 V and 29.5 eV −1 , respectively. In previous reports [23,24], the calculated A value of the a-IGZO system by MN rule was in the range of 19-24.3 eV -1 , which varied by process condition and/or G/I material. The total DOS distribution for three devices deposited at different pressures was calculated, as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The temperature-dependent field effect data were used to calculate the near conduction band. We observed that the drain current (ID) is thermally activated and can be described by [23,24] …”
Section: Resultsmentioning
confidence: 99%